2018
DOI: 10.1111/cei.13243
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s syndrome as a tool to dissect the mechanisms of thrombo-inflammation: clinical and pathogenetic aspects

Abstract: Summary Behçet’s syndrome (BS) is a complex disease with different organ involvement. The vascular one is the most intriguing, considering the existence of a specific group of patients suffering from recurrent vascular events involving the venous and, more rarely, the arterial vessels. Several clinical clues suggest the inflammatory nature of thrombosis in BS, especially of the venous involvement, thus BS is considered a model of inflammation‐induced thrombosis. Unique among other inflammatory conditions, veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 105 publications
(118 reference statements)
1
40
0
1
Order By: Relevance
“…Superficial venous thrombosis (SVT) and deep vein thrombosis (DVT) are the most frequent vascular manifestations of BS, affecting altogether up to 40% of patients (31,(68)(69)(70). DVT mainly involves the inferior, but also the superior limbs, while venous thrombosis of atypical locations (TAL) have been described (31,(69)(70)(71). At the cerebral level, non-parenchymal vascular central nervous system (CNS) involvements include cerebral venous sinus thrombosis (CVST), arterial occlusion, and/or aneurysms (72).…”
Section: Extra-parenchymal Neurological and Peripheral Vascular Phenomentioning
confidence: 99%
“…Superficial venous thrombosis (SVT) and deep vein thrombosis (DVT) are the most frequent vascular manifestations of BS, affecting altogether up to 40% of patients (31,(68)(69)(70). DVT mainly involves the inferior, but also the superior limbs, while venous thrombosis of atypical locations (TAL) have been described (31,(69)(70)(71). At the cerebral level, non-parenchymal vascular central nervous system (CNS) involvements include cerebral venous sinus thrombosis (CVST), arterial occlusion, and/or aneurysms (72).…”
Section: Extra-parenchymal Neurological and Peripheral Vascular Phenomentioning
confidence: 99%
“…Recent experimental data from our group have revealed that ROS-mediated modifications of the fibrinogen structure reflect alteration in its biological activity. Indeed, fibrinogen oxidation contributes to the formation of a more thrombogenic clot, mainly consisting of a tight fibrin network composed of filaments which are resistant to plasmin-induced lysis and with slightly decreased fiber size [12,13]. This deeply modified fibrin network can significantly contribute to vascular occlusion and thrombus development [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several clinical clues suggesting the inflammatory nature of thrombosis in BD, especially of the venous involvement, thus BD is considered a model of inflammation -induced thrombosis. [22][23]…”
Section: Etiopathogenesismentioning
confidence: 99%